REFLEKSI BUDAYA SUNDA TERHADAP SUPORTER WANITA ANALISIS KARAKTERISTIK SUPORTER WANITA SEPAKBOLA PERSIB - Sutresna, Nina; Berliana, Berliana; Sya'rani, Ahmad Zaeri; rizkia, fikri (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. This research examines female Indonesian football supporters. Data was collected through in-depth interviews (direct, personal and unstructured interviews) with 134 respondents. Based on research results, the characteristics of female supporters are very diverse. The age of female supporters consists of 27% under 17 years old, 43% aged 17-30 years old, and 30% over 30 years old. In this study, it is hoped that it can provide a clear picture of the length of time being a supporter, the motivations they have as a football supporter, and support from the surrounding environment. It is hoped that it can be one of the guidelines to provide a picture of the supporter development model. Materials and Methods. The research method used was a qualitative approach. Data were extracted through interpretative phenomenological analysis. Results. Supporters' background, gender, and socio-demographic issues are related to their behavior in showing loyalty to their favorite team. Conclusions. Basically, football supporters in Indonesia have great fanaticism both in men and women. Now this development is getting stronger because of the ease of access to watch at the stadium and make watching football as recreation on the weekend. The conclusion obtained in this study can be said that when fanaticism is directed in a better direction, it will produce a greater sense of fanaticism. In addition, providing good facilities and security will increase women's interest in coming to the stadium.